The Effect Of A Modern Tax Administration System Based On E-Samsat On Motor Vehicle Tax Compliance At The Samsat Office, Sumedang - Elis Nurhayati; Ayi Yuniawati; Sophia Annisa (LPPM Universitas Sebelas April, 2020)
This study aims to determine whether there is an influence of the e-samsat-based modern taxation system on Motor Vehicles taxpayer compliance at the SAMSAT Sumedang office and how much influence the administration system has on taxpayer compliance. This research is a quantitative study, the sample in this study were 100 taxpayers registered at the SAMSAT Sumedang Office. Collection techniques using a questionnaire that has been tested for validity and reliability. The data analysis technique used to answer hypotheses is simple linear regression. The results of the data analysis are seen from the results of the coefficient of determination test, to find out the amount of contribution provided by the modern tax administration system based on e-Samsat to motor vehicle taxpayer compliance by 60.5%.